Analisis Pengelolaan Keuangan Ditinjau dari Aspek Kas, Biaya Produksi dan Piutang pada Perusahaan Dagang - Helsi, Helsi Defiani Putri; Sajjaj, Muh. Sajjaj Sudirman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This research is motivated by the lack of a structured financial recording and management system that has an impact on the effectiveness of the company's operations. This study aims to analyze financial management in terms of cash, production costs and receivables in the trading company PD. Pada Lancar in Garut Regency. This study applies a qualitative approach using a descriptive method. The data collection process is carried out through in-depth interviews and direct observation in the field. Informants in this study consisted of business owners and managers who were directly involved in financial management activities. Data analysis was carried out using interactive analysis techniques that included the process of data reduction, data presentation and systematic conclusion drawing. The results of the study indicate that the cash aspect is managed manually without systematic recording, production costs often exceed estimates due to the absence of standard cost calculations and receivables are often not collected on time due to weak monitoring systems. This study concludes that an understanding and application of a simple financial recording system is needed to support business continuity. The implications of these findings indicate the importance of basic accounting education for business actors to improve effectiveness and efficiency in financial management.